Study on the Mix of Slurry Membrane for Soil Conditioning of EPB Shield and Its Application Effect in Water-Rich Gravel Strata. (24th March 2022) - Zhao, Jinpeng; Tan, Zhongsheng; Yu, Rongsen; Jia, Aidong; Qu, Chao
Abstract : The water inrush and large surface settlement encountered by EPB shield crossing water-rich gravel layer have attracted much attention. Based on the section tunnel engineering of the Inner Mongolia University South Campus Station-Xilin Park Station of line 2 of Hohhot Rail Transit, the optimum mix proportion of bentonite slurry and foam diluent for forming slurry membrane in water-rich gravel stratum was studied in this study at first. The characteristics of conditioned soil were analyzed in combination with slag soil. The water plugging effect and surface settlement with or without slurry membrane were investigated with numerical simulation. The numerical model has been effectively verified by comparing the field monitoring and numerical simulation of surface settlement value. Further, the water shutoff mechanism of the slurry membrane is revealed. The setting of the slurry membrane exhibited a good water plugging effect and effectively decreased the surface settlement. The construction method of "water plugging with a slurry membrane" proposed in this study could powerfully combine the respective advantages of EPB shield and slurry balance shield, ensuring the safety, high quality, and high efficiency of tunnel construction.